Assessment of genotoxic activity of oleoresins and leaves extracts of six Copaifera species for prediction of potential human risks. (15th July 2018) - Furtado, Ricardo Andrade; de Oliveira, Pollyanna Francielli; Senedese, Juliana Marques; Ozelin, Saulo Duarte; de Souza, Larissa Daniela Ribeiro; Leandro, Luís Fernando; de Oliveira, Wendel Luiz; da Silva, Jonas Joaquim Mangabeira; Oliveira, Larissa Costa; Rogez, Hervé; Ambrósio, Sérgio Ricardo; Veneziani, Rodrigo Cassio Sola; et al.
Abstract: Ethnopharmacological relevance: Copaifera species are used in folk medicine for a wide variety of pharmacological properties. This paper reports the cytotoxic and genotoxic analyses of oleoresins and leaves extracts of Copaifera species: C. duckei, C. multijuga, C. paupera, C. pubiflora, C. reticulata and C. trapezifolia . Materials and methods: In vitro assays were performed using Chinese hamster lung fibroblasts (V79 cells). The clonogenic efficiency and cytokinesis-block micronucleus assays were employed for the cytotoxicity and genotoxicity assessment, respectively. The mouse bone marrow micronucleus test was used for in vivo studies. Results: The cytotoxicity results using the clonogenic efficiency assay showed IC50 values ranging from 9.8 to 99.2 µg/mL for oleoresins and 66.4–721.5 for leaves extracts. However, no cytotoxic effect was observed in the in vivo studies. Additionally, the treatments with oleoresins and leaves extracts did not significantly increase the frequency of micronuclei in both in vitro and in vivo mammalian cells. The UPLC-MS/MS and CG/MS analyses of Copaifera oleoresins allowed the identification of 10 acid diterpenes and 11 major volatile sesquiterpenes. Leaves are rich in phenolic compounds including two flavonoid heterosides and 16 galloylquinic acid derivatives. Conclusions: The oleoresins and leaves extracts of studied Copaifera species were not cytotoxic in vivo, as well as not genotoxic in both in vitro and vivo assays, under the experimental conditions used. Therefore, the obtained results should be sufficient to demonstrate the absence of significant genotoxic risk of these Copaifera products for human use in the evaluated concentrations range. Graphical abstract: